Redesign The Relevance Of Justice In Debtor Protection Related To Parate Executions Performed By Separate Creditors In Liability Agreements - Binov Handitya (Jurnal Akta, 2021)
The existence of Articles 55 and 56 of Act No. 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations, the position of debtor protection in the implementation of bankruptcy carried out by separatist creditors against creditors is weak, this is due to the absence of legal remedies that can be taken by debtors during bankruptcy has been found to have happened to him. Therefore, it is necessary to have a disposition of justice in protecting debtors from the rights of separatist creditors. The implementation of bankruptcy as referred to in Article 55 and Article 56 of Act No. 37 of 2004 has not been fair to the debtor, considering that the two articles are only based on the existence of debt from the debtor and are related to the position of solvent or insolvency based on the creditor's view alone. This is clearly the case because Act No. 37 of 2004 does not adhere to a balance sheet test system where before being declared bankrupt it is necessary to test the condition of the debtor whether it is really insolvent or actually still solvent. 2) The factors that have resulted in bankruptcy law so far have not been fair to debtors are legal factors, namely in the form of the provisions of Article 55 and Article 56 of Act No. 37 of 2004 which are unfair to debtors the law even though it is widely known that the door to justice in bankruptcy cases is the judge's decision. 3) Therefore, it is necessary to reconstruct Article 55 and Article 56 of Act No. 37 of 2004.